Graduates of Private Schools and the Greek University: Empirical data and sociological interpretations through the period of crisis - Fotopoulos, Nikos Fotopoulos; Zagkos, Christos; Fatourou, Polina (Advances in Social Sciences Research Journal, 2020)
Ιn modern Greece, the entrance in higher education is considered a kind of social ’fetish’. In this concept, the Greek family diachronically strives to provide its members with an academic perspective, even if this parental choice is linked to many economic and psychological sacrifices. Private education is often associated with the perspective of a better academic and career prospect which is necessarily linked to entrance procedures at the Greek university. During the period (2001-2011) the representation of private school graduates in the total student population seems to be under "representative normality”. Additionally, private school students appear to have the same overall possibilities (neither less nor more) with public school graduates into higher education. However, a deeper sociological analysis demonstrates significant differences in the representation of higher education between public and private schools. This report focuses on private school graduates and more generally on the interpretation of how their entrance into higher education is portrayed.